PENDAMPINGAN GURU SD PENGGILINGAN 01 JAKARTA DALAM MENDESAIN E-MODUL FLIPPED BOOK UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA - Irma Savitri Sadikin; Imam Santosa; Lutfiyah Lutfiyah; Hardianti Hardianti; Muhammad Rijal Fadli (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service program aimed to enhance the digital and pedagogical competencies of teachers at SD Penggilingan 01 Jakarta through training and mentoring on the development of digital learning materials using the flipped book approach. The program was conducted over four months (October 2024–January 2025) and involved 20 teachers from various grade levels. The implementation process included four main stages: needs assessment, training and workshop, classroom mentoring, and evaluation.The pre–post test results indicated an average improvement of 47.6% in teachers’ competencies, covering the understanding of digital media design skills and multimedia integration. Ninety percent of the participants successfully created their own flipped books relevant to their teaching subjects. Teachers also demonstrated greater confidence and creativity in integrating digital tools into their lessons. The impact was evident on three levels: teachers became more innovative, students showed higher enthusiasm and learning independence, and the school gained a sustainable digital learning model. This program highlights that flipped book–based training is an effective pedagogical strategy to support the implementation of the Merdeka Curriculum and foster a more adaptive digital learning ecosystem in elementary education.